Endoscopic submucosal excavation for gastric muscularis propria tumours less than 10 mm in diameter: What are the risk factors responsible for perforation? - Liu, Zhaohui; Li, Hualin; Deng, Jiwen; Wu, Ruinuan (PloS one, 2025)
To explore the risk factors for perforation during endoscopic submucosal excavation (ESE) for gastric muscularis propria tumours less than 10 mm in diameter. This study provides clinical guidance for preventing the occurrence of intraoperative adverse events. Samples of gastric muscularis propria tumours less than 10 mm in diameter were removed via ESE at Shenzhen Second People's Hospital and were collected from June 2023 to August 2024. The general clinical characteristics of the patients, location, size, growth pattern, and pathology of the tumours, operation time, resection time, perforation incidence and bleeding incidence were analysed, and logistic regression was used to calculate the risk factors for perforation and bleeding. A total of 102 patients were included in this study. The tumours were successfully removed from all patients. The mean age was 52.28 ± 11.84 years. There were 34 (33.33%) males. The mean size was 6.96 ± 1.82 mm. 89 (87.25%) tumours exhibited an intraluminal growth pattern. In total, 79 (77.45%) tumours were in the gastric body, and 23 (22.55%) tumours were in the gastric fundus. The mean operation time was 35.26 ± 23.15 min, and the mean resection time was 27.88 ± 21.77 min. A total of 55 (53.92%) tumours were leiomyoma, and 43 (42.16%) tumours were GIST. There were 4 (3.92%) tumours classified as other lesions. 41 (40.20%) patients experienced intraoperative bleeding, all of which had minor bleeding and successful haemostasis under endoscopy.There were 27 (26.47%) concurrent perforation, of which,24(88.89%) were diagnosed as GIST, and 3(11.11%) were diagnosed as leiomyoma. All perforations were successfully managed with an endoscopic suture. According to the multivariate regression analysis, a pathologic diagnosis was a risk factor for perforation. When the pathological diagnosis is GIST, the risk of perforation increases (PE = 18.632, 95% CI 4.571 ~ 75.941; p < 0.001). Gender,age,tumor size, growth pattern, location, and resection time were not found to be risk factors for perforation.all of observed factors were not the risk factors for bleeding. ESE is an effective removal method for gastric muscularis propria tumours less than 10 mm in diameter.Intraoperative bleeding and perforation are common.However, these complications are controllable.GIST is an independent risk factor for the perforation.When the tumour is diagnosed as a GIST, the incidence of perforation is significantly increased.